Swamy's manual for procurement of consultancy and other services - Muthuswamy; Brinda; Sanjeev (Chennai Swamy publishers, 2024)
This book is about the procurement of consultancy and other services with relevant decisions of the government under the respective chapters.
Keywords: Consultancy services